THE STAGES OF MORAL REASONING TOWARD CHEATING BEHAVIOR ON UNDERGRADUATE STUDENTS OF GUIDANCE AND COUNSELING IN STATE UNIVERSITY OF PADANG - S. Rumapea, Roida (Jurnal Konselor, 2015)
This research was aimed at describing: (1) the studentsâ moral reasoning level, (2) the difference between moral reasoning level of the students enrolled in 2014 and in 2012, and (3) the difference between moral reasoning level of male and female students. This research applied quantitative approach and descriptive comparative method. The research findings indicated that: (1) the studentsâ moral reasoning ability were in conventional level, (2) there was no significant difference between moral reasoning level of the students enrolled in 2014 and in 2012, and (3) ) there was no significant difference between moral reasoning level of male and female students.Â Keywords: moral reasoning, cheating